Power, interest and insecurity: A comparative analysis of workplace dualization and inclusion in Europe - Arthur Corazza (London School of Economics and Political Science (LSE), European Institute, 2020)
In Europe's 'age of dualisation', interest groups are key to contemporary political economy theory of insider-outsider divides, where only strategic, rational choice might explain a shift to inclusive representation. Yet, a recent and growing body of case studies argues that power dynamics shape preferences, strategies and, ultimately, workplace inequalities. This paper draws on theoretical developments to examine these competing hypotheses. In particular, it seeks to identify the conditions under which workplace-level representation moderates or reinforces subjective insecurity gaps between stable and atypical employment. Through an explanatory sequential mixed methodology, multi-level logistic regression using survey data maps out the set of EU28 political economies while a qualitative section compares two cases in depth. Overall, the findings reveal country clusters that support the power-based thesis, based on institutional and ideational resources, and run counter the rational choice argument. Integrated into the 'vicious circle' concept, adverse conditions specify endogenous relationships at a certain threshold, but can be disqualified as sine qua non catalysers. The paper therefore contributes to the 'varieties of workplace dualisation' literature, connecting the angle of employment relations with political economy research on inequalities.
Keywords: 330; Dualisation; atypical work; employment insecurity; industrial relations; political economy